Uso de águas salinas no cultivo de forrageiras - Praxedes, Saulo Samuel Carneiro (Universidade Federal Rural do Semi-Árido, 2013)
Brazil has high potential for forage production, rightfully be located in a tropical climate region. In the Brazilian Northeast irrigation of pastures has been implemented as a way to compensate for the lack of rain for most of the year.The scarcity of good quality waterand increasing their demand to meet the population growth has led to the use of water sources of lower quality, among which the saline water, very common in semiarid regions. Forage crops are considered tolerant plants to salinity, being variables of growth and production very important factors to study the effects caused by salt stress. TheCynodon spp. cv. Tifton 85 andTanzania grass (Panicum maximum) are forages that have gained prominence in recent years, are often recommended to feed animals worldwide. Thus, in order to evaluate the performance of Tifton 85 and Tanzania grasses with the use of saline water and of two irrigation methods, grown in Alfissolof the semiarid region of Mossoró RN, developed this research in greenhouse at UFERSA, in experimental design completely randomized, with treatments in a factorial, with four replications. Treatments included a combination of two irrigation methods (drip and sprinkler)with five salinity levels of irrigation water (S1=0,5; S2=1,5; S3=2,5; S4=3,5 e S5=4,5 dS m-1). Evaluated the yield components height (ALT), fresh biomass (FMF) and dry biomass (FMS) of shoots of Tifton 85 and Tanzaniagrasses, plus tiller number (NP) and leaf area (AF) of Tanzania grass.Monitoring was conducted soil salinity, being determined over the cycle the electrical conductivity of the saturation extract (CEes), the RAS and the pH of soils under grasses. In a generalized form, irrigation water with high salinity inhibited the growth of plants Tifton 85, reduced the FMF and FMS of Tifton 85 and Tanzania grasses and reduced the NP and AF Tanzania grass, however, is possible to obtain good yields CEa with a maximum of 2.8 dS m-1. The increase in salinity resulted in a linear increase of CEes and soil RAS, as well, caused a reduction in the soil pH. The method of drip irrigation method was superior to sprinkler irrigation in the production of Tanzania grass when using higher salinity water
Use of saline waters in the cultivation of fodder
Keywords: Panicum maximum; Cynodonspp; Tifton 85; Irrigation methods; Electrical conductivity; Panicum maximum; Cynodonspp; Tifton 85; Métodos de irrigação; Condutividade elétrica; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM